Short- and long-term effects of hemodialysis on platelet and monocyte activity markers of atherosclerosis in patients with end-stage renal disease - Benck, Urs Tobias; Stach-Jablonski, Ksenija; Jung, Susanne Claudia; Krämer, Bernhard; Kälsch, Thorsten; Kälsch, Anna-Isabelle (Cardiology journal, 2017)
Background: In hemodialysis (HD) patients cardiovascular events represent the predominant cause of mortality. Since platelet and monocyte activity markers play an important role in cardiovascular mortality, this study assessed the influence of HD on these markers.
Gesehen am 03.04.2018